Compound containing phenanthroline and cyano structure and laminated organic electroluminescent device thereof

By using compounds containing orthophenolone and cyano structures as charge generation layer materials in organic electroluminescent devices, the problem of insufficient injection capacity of electron transport layer is solved, and lower driving voltage and higher efficiency are achieved. The life span and the formation of coordination bonds with metal enhances the stability of the device.

CN119219622APending Publication Date: 2024-12-31JIANGSU SUNERA TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310773834.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

There is still room for improvement in the luminous efficiency and service life of existing organic electroluminescent devices in applications, especially the injection and transmission capabilities of the electron transport layer, which leads to high driving voltage and poor heat resistance and film stability, affecting device performance. and lifespan.

Method used

Compounds containing orthophenolone and cyano structures are used as charge generation layer materials, and connected through specific connecting units to achieve good electron injection and transmission capabilities, and form coordination coupling with metals to reduce device driving voltage, improve efficiency and life.

Benefits of technology

It effectively reduces the device driving voltage, improves electron injection and transmission capabilities, improves device efficiency and life, and inhibits metal oxidation and enhances device stability by forming stable N-metal coordination bonds with metal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219622A_ABST
    Figure CN119219622A_ABST
Patent Text Reader

Abstract

The invention discloses a compound containing phenanthroline and cyano structures and a laminated organic electroluminescent device thereof, and belongs to the technical field of semiconductor materials. The structure of the compound is as shown in a general formula (1): # imgabs0 #. The compound containing phenanthroline and cyano structures can be applied to a charge generation layer of an organic electroluminescent device. According to the compound, phenanthroline and cyano structural units are connected through a specific structural unit, the formed compound has good electron injection and transmission capacity and good electron tolerance and stability, and when the compound is used as a material of an organic electroluminescent device, under low driving voltage, the compound can be used for preparing the organic electroluminescent device. And good efficiency and service life are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of semiconductor materials, in particular to a compound containing o-phenanthroline and cyano structures and a laminated organic electroluminescent device thereof. Background Art

[0002] Organic light emitting diode (OLED) technology can be used to manufacture new display products as well as new lighting products. It is expected to replace existing liquid crystal displays and fluorescent lighting, and has a wide range of applications. Organic light emitting diodes have a sandwich-like structure, including electrode material films and organic functional materials sandwiched between different electrode material films. Various organic functional materials are superimposed on each other according to their uses to form organic light emitting diodes. As a current device, when voltage is applied to the electrodes at both ends of the organic light emitting diode and the electric field acts on the positive and negative charges in the organic layer functional material film layer, the positive and negative charges further recombine in the light emitting layer, generating organic electroluminescence.

[0003] Currently, organic electroluminescent display technology has been applied in smart phones, tablet computers and other fields, and will be further expanded to large-size application fields such as televisions. However, compared with the actual product application requirements, the performance of organic electroluminescent devices such as luminous efficiency and service life needs to be further improved. In order to continuously improve the performance of organic electroluminescent devices, it is necessary to continuously research and innovate optoelectronic functional materials to create higher performance organic electroluminescent functional materials.

[0004] The optoelectronic functional materials used in organic electroluminescent devices can be divided into two categories based on their uses, namely charge injection transport materials and luminescent materials. Furthermore, charge injection transport materials can be divided into electron injection transport materials, electron blocking materials, hole injection transport materials and hole blocking materials. As charge transport materials, they are required to have good carrier mobility, high glass transition temperature, etc. For organic electroluminescent devices, electrons are injected from the cathode and then transferred to the main material through the electron transport layer, where they recombine with holes to generate excitons. Therefore, improving the injection and transport capabilities of the electron transport layer is conducive to reducing the device driving voltage and obtaining efficient electron-hole recombination efficiency.

[0005] In addition, the stacked organic electroluminescent device is a device that connects two or more independent light-emitting units in series through a charge generation layer (CGL). Under the action of an external electric field, the electrons and holes generated by the charge generation layer (CGL) are respectively injected into adjacent light-emitting units, and are recombined into excitons in the light-emitting units to emit light. Therefore, the material selection and design of the charge generation layer (CGL) are key factors affecting the optoelectronic performance and life of the stacked device. The charge generation layer (CGL) is constructed in the form of a pn structure, in which the p-type doped material mainly generates holes, such as materials such as F4-TCNQ and HAT-CN, while the n-type doped material is doped with a low work function metal through the electron transport layer material, such as Alq3:Mg and Bphen:Li. Therefore, the performance of the electron transport material of the n-type doped material in the charge generation layer (CGL) has a very large impact on the device performance. It is required to have efficient electron injection ability, transport ability and high electronic durability. At the same time, the heat resistance and film stability of the material are also important. Materials with low heat resistance are not only prone to decomposition during material evaporation, but also thermally decomposed by the heat generated by the device when the device is working, causing material degradation. In the case of poor phase stability of the material film, the material will also undergo thin film crystallization in a short period of time, resulting in direct layer separation of the organic film layer and device degradation. Therefore, the materials used are required to have high heat resistance and good film stability.

[0006] With the remarkable progress of OLED devices, the performance requirements for charge generation layer materials are also increasing. Not only are they required to have good material stability, but they are also required to achieve good efficiency and life at low driving voltage. Summary of the invention

[0007] In view of the above problems existing in the prior art, the present invention provides a compound containing o-phenanthroline and cyano structures and a stacked organic electroluminescent device thereof. In the compound of the present invention, o-phenanthroline and cyano are connected by a specific connecting unit. The compound has good electron injection and transmission capabilities, and can form a coordination coupling effect with a metal to achieve good electron injection and transmission, while achieving an excellent charge generation layer effect (Charge Generation Layer). When used in a stacked OLED device, the device driving voltage can be effectively reduced, and the device efficiency and life can be improved.

[0008] A compound containing o-phenanthroline and a cyano structure, wherein the structure of the compound containing o-phenanthroline and a cyano structure is shown in general formula (1):

[0009]

[0010] In the general formula (1), X 1 , X2 , X 3 , X 4 , X 5 , X 6 Each independently represents CH or N; X 1 , X 2 , X 3 , X 4 , X 5 , X 6 At most one of them is represented by N; Ar 1 ,Ar 2 Each independently represents a substituted or unsubstituted phenyl group, a substituted or unsubstituted naphthyl group, a substituted or unsubstituted biphenyl group, a substituted or unsubstituted terphenyl group, a substituted or unsubstituted pyridyl group or a structure represented by the general formula (2); Ar 1 ,Ar 2 There is only one structure represented by general formula (2); L 1 , L 2 , L 3 Each independently represents a single bond, a substituted or unsubstituted phenylene group, a substituted or unsubstituted naphthylene group, a biphenylene group, a substituted or unsubstituted terphenylene group, or a substituted or unsubstituted pyridylene group; L 1 , L 2 , L 3 Can be the same or different;

[0011] In the general formula (2), R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 , R 8 Each independently represents a hydrogen atom, a substituted or unsubstituted C1-C6 alkyl group, a substituted or unsubstituted phenyl group, or a substituted or unsubstituted naphthyl group, R 1 -R 8 At least one of them is absent to serve as a linking site;

[0012] The substituent of the substitutable group may be selected from deuterium, tritium, halogen, cyano, C1-C6 alkyl or phenyl.

[0013] Furthermore, the structure of the compound containing o-phenanthroline and cyano structure is shown in general formula (1-1):

[0014]

[0015] In the general formula (1-1), X 1 , X 2 , X 3 , X 4 , X5 , X 6 Each independently represents CH or N; X 1 , X 2 , X 3 , X 4 , X 5 , X 6 At most one of them is represented by N; Ar 2 L represents substituted or unsubstituted phenyl, substituted or unsubstituted naphthyl, substituted or unsubstituted biphenyl, substituted or unsubstituted terphenyl, substituted or unsubstituted pyridyl; 3 represented by substituted or unsubstituted phenylene, substituted or unsubstituted naphthylene, biphenylene, substituted or unsubstituted terphenylene, substituted or unsubstituted pyridylene;

[0016] R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 , R 8 Each independently represents a hydrogen atom, a substituted or unsubstituted C1-C6 alkyl group, a substituted or unsubstituted phenyl group, or a substituted or unsubstituted naphthyl group, R 1 -R 8 At least one of them is absent to serve as a linking site;

[0017] The substituents of the substitutable group are optionally selected from protium, deuterium, tritium, halogen, cyano, C1-C6 alkyl or phenyl;

[0018] Furthermore, the structure of the compound containing o-phenanthroline and a cyano structure is shown in general formula (1-2):

[0019]

[0020] In the general formula (1-2), X 1 , X 2 , X 3 , X 4 , X 5 , X 6 Each independently represents CH or N; X 1 , X 2 , X 3 , X 4 , X 5 , X 6 At most one of them is represented by N; Ar 2 L represents substituted or unsubstituted phenyl, substituted or unsubstituted naphthyl, substituted or unsubstituted biphenyl, substituted or unsubstituted terphenyl, substituted or unsubstituted pyridyl; 3represented by substituted or unsubstituted phenylene, substituted or unsubstituted naphthylene, biphenylene, substituted or unsubstituted terphenylene, substituted or unsubstituted pyridylene;

[0021] R 2 , R 3 , R 4 , R 5 , R 6 , R 7 , R 8 Each independently represents a hydrogen atom, a substituted or unsubstituted C1-C6 alkyl group, a substituted or unsubstituted phenyl group, or a substituted or unsubstituted naphthyl group, R 1 -R 8 At least one of them is absent to serve as a linking site;

[0022] The substituent of the substitutable group may be selected from deuterium, tritium, halogen, cyano, C1-C6 alkyl or phenyl.

[0023] Furthermore, the structure of the compound containing o-phenanthroline and a cyano structure is shown in any one of general formulas (1-3) to (1-6):

[0024]

[0025]

[0026] In the general formula (1-3) to the general formula (1-6), X 1 , X 2 , X 3 , X 4 , X 5 , X 6 Each independently represents CH or N; X 1 , X 2 , X 3 , X 4 , X 5 , X 6 At most one of them is represented by N; Ar 2 L represents substituted or unsubstituted phenyl, substituted or unsubstituted naphthyl, substituted or unsubstituted biphenyl, substituted or unsubstituted terphenyl, substituted or unsubstituted pyridyl; 3 represented by substituted or unsubstituted phenylene, substituted or unsubstituted naphthylene, biphenylene, substituted or unsubstituted terphenylene, substituted or unsubstituted pyridylene;

[0027] R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R7 , R 8 Each independently represents a hydrogen atom, a substituted or unsubstituted C1-C6 alkyl group, a substituted or unsubstituted phenyl group, or a substituted or unsubstituted naphthyl group, R 1 -R 8 At least one of them is absent to serve as a linking site;

[0028] The substituent of the substitutable group may be selected from deuterium, tritium, halogen, cyano, C1-C6 alkyl or phenyl.

[0029] Furthermore, the structure of the compound containing o-phenanthroline and a cyano structure is as shown in any one of general formulas (1-7) to (1-10):

[0030]

[0031] In the general formula (1-7) to the general formula (1-10), X 1 , X 2 , X 3 , X 4 , X 5 , X 6 Each independently represents CH or N; X 1 , X 2 , X 3 , X 4 , X 5 , X 6 At most one of them is represented by N; Ar 2 L represents substituted or unsubstituted phenyl, substituted or unsubstituted naphthyl, substituted or unsubstituted biphenyl, substituted or unsubstituted terphenyl, substituted or unsubstituted pyridyl; 3 represented by substituted or unsubstituted phenylene, substituted or unsubstituted naphthylene, biphenylene, substituted or unsubstituted terphenylene, substituted or unsubstituted pyridylene;

[0032] R 2 , R 3 , R 4 , R 5 , R 6 , R 7 , R 8 Each independently represents a hydrogen atom, a substituted or unsubstituted C1-C6 alkyl group, a substituted or unsubstituted phenyl group, or a substituted or unsubstituted naphthyl group, R 1 -R 8 At least one of them is absent to serve as a linking site;

[0033] The substituent of the substitutable group may be selected from deuterium, tritium, halogen, cyano, C1-C6 alkyl or phenyl.

[0034] Furthermore, in the general formula (1), the L1 , L 2 , L 3 Independently selected from any one of the following structures:

[0035] single bond,

[0036] Furthermore, the L 1 , L 2 , L 3 Independently selected from any one of the following structures:

[0037] single bond,

[0038] Furthermore, the Ar 1 ,Ar 2 Independently selected from any one of the following structures:

[0039] And the Ar 1 ,Ar 2 There is only one representation of any of the following structures:

[0040]

[0041] Further, the compound containing o-phenanthroline and a cyano structure is any one of the following structures:

[0042]

[0043]

[0044]

[0045]

[0046]

[0047]

[0048]

[0049]

[0050]

[0051]

[0052]

[0053]

[0054]

[0055]

[0056]

[0057]

[0058]

[0059]

[0060]

[0061]

[0062]

[0063] The present invention also discloses a stacked organic electroluminescent device, comprising a first electrode, a second electrode, a first light-emitting unit, a second light-emitting unit and a charge generating layer, wherein the first light-emitting unit, the second light-emitting unit and the charge generating layer are located between the first electrode and the second electrode, the charge generating layer is located between the first light-emitting unit and the second light-emitting unit, and the charge generating layer comprises the compound containing o-phenanthroline and a cyano structure.

[0064] Furthermore, the first light-emitting unit includes a first hole transport region, a first light-emitting layer and a first electron transport region, and the second light-emitting unit includes a second hole transport region, a second light-emitting layer and a second electron transport region.

[0065] Furthermore, the first hole transport region comprises a first hole injection layer, a first hole transport layer, and a first electron blocking layer; the first electron transport region comprises a first hole blocking layer and a first electron transport layer; the second hole transport region comprises a second hole injection layer, a second hole transport layer, and a second electron blocking layer; the second electron transport region comprises a second hole blocking layer, a second electron transport layer, and a second electron injection layer.

[0066] Furthermore, the charge generation layer also contains a metal material.

[0067] Furthermore, the metal material is Li, Ca, Ag, Cs or Yb.

[0068] The beneficial technical effects of the present invention are:

[0069] (1) In the compound of the present invention, the o-phenanthroline and the cyano group are connected by a phenyl group or an azabenzene derivative, which has good electron injection and transmission capabilities and can effectively improve electron injection and transmission, thereby reducing the device driving voltage and improving the device efficiency.

[0070] (2) The compound containing o-phenanthroline and cyano structure described in the present invention has good electron-withdrawing ability, film stability and electron tolerance. When used as an n-type material of the charge generation layer (CGL layer), it can form a stable N-metal coordination bond with metals such as Yb to form a stable and flat organic-metal doped film, which inhibits the oxidation of the metal and is beneficial to improving the charge generation efficiency and device stability.

[0071] (3) When the compound of the present invention is used as an organic electroluminescent functional layer material in an OLED device, it can effectively reduce the device driving voltage and increase the device life. It has a good application effect in OLED light-emitting devices and has a good industrialization prospect. BRIEF DESCRIPTION OF THE DRAWINGS

[0072] Figure 1 is a schematic diagram of the structure of the stacked organic electroluminescent device described in the embodiment;

[0073] In the figure: 1, substrate layer; 2, anode layer; 3, first hole injection layer; 4, first hole transport layer; 5, first electron blocking layer; 6, first light-emitting layer; 7, first hole blocking layer; 8, first electron transport layer; 9, charge generation layer; 10, second hole injection layer; 11, second hole transport layer; 12, second electron blocking layer; 13, second light-emitting layer; 14, second hole blocking layer; 15, second electron transport layer; 16, second electron injection layer; 17, cathode layer; 18, covering layer. DETAILED DESCRIPTION

[0074] The specific implementation of the present invention is described in detail below. The present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed.

[0075] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and are not intended to limit the present invention.

[0076] In this application, unless otherwise specified, HOMO means the highest occupied orbital of a molecule, and LUMO means the lowest unoccupied orbital of a molecule. In addition, in the present invention, HOMO and LUMO energy levels are expressed in absolute values, and the comparison between energy levels is also a comparison of the magnitude of their absolute values. Those skilled in the art know that the greater the absolute value of an energy level, the lower the energy of the energy level.

[0077] In the accompanying drawings, the dimensions of layers and regions may be exaggerated for clarity. It will also be understood that when a layer or element is referred to as being "above" another layer or substrate, the layer or element may be directly above the other layer or substrate, or there may be intervening layers. In addition, it will be understood that when a layer is referred to as being "between" two layers, the layer may be the only layer between the two layers, or there may be one or more intervening layers. The same reference numerals throughout the text represent the same elements.

[0078] In this application, when describing electrodes and organic electroluminescent devices, as well as other structures, the words "upper" and "lower" used to indicate orientation only indicate orientation in a certain state, and do not mean that the related structure can only exist in the described orientation; on the contrary, if the structure can change its position, such as being inverted, the orientation of the structure will be changed accordingly. Specifically, in the present invention, the "lower" side of the electrode refers to the side of the electrode close to the substrate during the preparation process, and the opposite side away from the substrate is the "upper" side.

[0079] The C of the present invention 1 -C 6 The alkyl group (including linear alkyl groups and branched alkyl groups) refers to methyl, ethyl, propyl, isopropyl, butyl, tert-butyl, isobutyl, sec-butyl, neopentyl, n-pentyl, isopentyl, 1-methylpentyl and the like, but is not limited thereto.

[0080] Laminated organic electroluminescent device:

[0081] The stacked organic electroluminescent device of the present invention may include a substrate layer, an anode layer, a first hole injection layer, a first hole transport layer, a first electron blocking layer, a first light-emitting layer, a first hole blocking layer, a first electron transport layer, a charge generating layer, a second hole injection layer, a second hole transport layer, a second electron blocking layer, a second light-emitting layer, a second hole blocking layer, a second electron transport layer, a second electron injection layer, a cathode layer and a covering layer. If the above layers exist, the anode layer is above the substrate layer, the first hole injection layer is above the anode layer, the first hole transport layer is above the first hole injection layer, the first electron blocking layer is above the first hole transport layer, and the first electron blocking layer is above the first hole transport layer. A light-emitting layer is above the first electron blocking layer, the first hole blocking layer is above the first light-emitting layer, the first electron transport layer is above the first hole blocking layer, and the charge generation layer is above the first electron transport layer, wherein the second hole injection layer is above the charge generation layer, the second hole transport layer is above the second hole injection layer, the second electron blocking layer is above the second hole transport layer, the second light-emitting layer is above the second electron blocking layer, the second hole blocking layer is above the second light-emitting layer, the second electron transport layer is above the second hole blocking layer, the second electron injection layer is above the second electron transport layer, the cathode layer is above the second electron injection layer, and the capping layer is above the cathode layer.

[0082] As the substrate of the organic electroluminescent device of the present invention, any substrate commonly used in organic electroluminescent devices can be used. Examples are transparent substrates, such as glass or transparent plastic substrates; opaque substrates, such as silicon substrates; flexible PI film substrates. Different substrates have different mechanical strengths, thermal stability, transparency, surface smoothness, and waterproofness. Depending on the properties of the substrate, its use direction is different. In the present invention, a transparent glass substrate is preferably used, and the thickness of the substrate is not particularly limited.

[0083] As the anode material of the organic electroluminescent device of the present invention, non-limiting examples include, but are not limited to, indium tin oxide (ITO), indium zinc oxide (IZO), tin oxide (SnO 2 ), zinc oxide (ZnO), magnesium (Mg), aluminum (Al), silver (Ag), aluminum-lithium (Al-Li), calcium (Ca), magnesium-indium (Mg-In) and magnesium-silver (Mg-Ag). The anode layer may have a single-layer structure or a multilayer structure including two or more layers. In addition, the thickness of the anode layer depends on the material used, and is generally 50-500nm, preferably 70-300nm and more preferably 100-200nm.

[0084] The first hole injection layer and the second hole injection layer may comprise a main material and a P-type doping material, wherein the main material may be selected from conventional hole transport materials in the prior art, and the P-type doping material may be selected from compounds with charge conductivity disclosed in the prior art, and may be selected from compounds disclosed in the following patent documents: WO2011073149A, EP1968131A1, EP2276085A1, EP2213662A1, EP1722602A1, EP2045 848A1, DE102007031220A1, US20100181555A1, US20100102709A1, WO2009003455A1, WO2010094378A1, WO2011120709A1, US20100096600A1, DE102012209523A1, CN101728485A and WO2012095143A1, but are not limited thereto.

[0085] For example, the compound shown below:

[0086]

[0087] The thickness of the first hole injection layer and the second hole injection layer of the present invention may be 1-100 nm, preferably 2-50 nm, and more preferably 5-20 nm.

[0088] The materials of the first hole transport layer and the second hole transport layer are preferably materials having high hole mobility, which enables holes to be transferred from the anode or the hole injection layer to the light emitting layer.

[0089] Preferably, the hole transport material for the first hole transport layer and the second hole transport layer of the present invention may be selected from the following compounds disclosed in the prior art:

[0090]

[0091]

[0092] The thickness of the first hole transport layer and the second hole transport layer of the present invention may be 5-200 nm, preferably 10-180 nm, and more preferably 20-150 nm.

[0093] The electron blocking layer materials of the first electron blocking layer and the second electron blocking layer can be selected from the following compounds disclosed in the prior art:

[0094]

[0095] According to the present invention, the thickness of the first electron blocking layer and the second electron blocking layer may be 1-200 nm, preferably 5-150 nm, and more preferably 5-50 nm.

[0096] According to the present invention, the material of the first light-emitting layer and the second light-emitting layer is a material that can emit visible light by receiving holes from the hole transport region and electrons from the electron transport region, respectively, and combining the received holes and electrons. The first light-emitting layer and the second light-emitting layer may include a host material and a doping material. Among them, the host material can be one or a combination of two of anthracene derivatives, quinoxaline derivatives, triazine derivatives, xanthone derivatives, diphenyl ketone derivatives, carbazole derivatives, pyridine derivatives or pyrimidine derivatives. The guest material can be a pyrene derivative, a boron derivative, a chrysene derivative, a spirofluorene derivative, an iridium complex or a platinum complex.

[0097] The thickness of the first light-emitting layer and the second light-emitting layer of the present invention may be 5-60 nm, preferably 10-50 nm, and more preferably 20-45 nm.

[0098] As the hole blocking material of the first hole blocking layer and the second hole blocking layer of the organic electroluminescent device of the present invention, the hole blocking layer materials for organic electroluminescent devices disclosed in the following prior art can be used:

[0099]

[0100]

[0101] The thickness of the first hole blocking layer and the second hole blocking layer of the present invention may be 2-200 nm, preferably 5-150 nm, and more preferably 5-50 nm, but the thickness is not limited to this range.

[0102] As the electron transport material of the first electron transport layer and the second electron transport layer of the organic electroluminescent device of the present invention, the following compounds disclosed in the prior art can be used as electron transport layer materials of organic electroluminescent devices:

[0103]

[0104] In a preferred embodiment of the present invention, the first electron transport layer and the second electron transport layer further include other compounds conventionally used in electron transport layers, for example, Alq3, LiQ, preferably LiQ.

[0105] The thickness of the first electron transport layer and the second electron transport layer of the present invention may be 10-80 nm, preferably 20-60 nm, and more preferably 25-45 nm.

[0106] According to the present invention, as the first electron injection layer and the second electron injection layer materials of the organic electroluminescent device of the present invention, the electron injection layer materials for organic electroluminescent devices disclosed in the prior art can be used: LiF, Cs 2 CO 3 、CsF、Csq、NaF、MgF 2 , CaF 2 、Al 2 O 3 , Yb.

[0107] The thickness of the first electron injection layer and the second electron injection layer of the present invention may be 0.1-5 nm, preferably 0.5-3 nm, and more preferably 0.8-1.5 nm, but the thickness is not limited to this range.

[0108] According to the present invention, the material for forming cathode can be a material with low work function, such as metal, alloy, conductive compound or their mixture. Non-limiting examples of cathode materials can include lithium (Li), ytterbium (Yb), magnesium (Mg), aluminum (Al), calcium (Ca), and aluminum-lithium (Al-Li), magnesium-indium (Mg-In) and magnesium-silver (Mg-Ag). The thickness of cathode layer depends on the material used, typically 5-100nm, preferably 7-50nm and more preferably 10-25nm.

[0109] Optionally, in order to improve the light extraction efficiency of the organic electroluminescent device, a light extraction layer (ie, CPL layer) may be added on the cathode layer of the device. The following compounds disclosed in the prior art may be used as CPL layer materials.

[0110]

[0111] The thickness of the CPL layer is generally 5-300 nm, preferably 20-100 nm, and more preferably 40-80 nm.

[0112] The organic electroluminescent device may further include an encapsulation structure. The encapsulation structure may be a protective structure that prevents foreign substances such as moisture and oxygen from entering the organic layer of the organic electroluminescent device. The encapsulation structure may be, for example, a can, such as a glass can or a metal can; or a thin film covering the entire surface of the organic layer.

[0113] Organic electroluminescent device preparation method

[0114] The method for preparing the above-mentioned organic electroluminescent device of the present invention comprises sequentially laminating an anode layer, a first hole injection layer, a first hole transport layer, a first electron blocking layer, a first light-emitting layer, a first hole blocking layer, a first electron transport layer, a charge generating layer, a second hole injection layer, a second hole transport layer, a second electron blocking layer, a second light-emitting layer, a second hole blocking layer, a second electron transport layer, a second electron injection layer, a cathode layer and a covering layer on a substrate.

[0115] For lamination, vacuum deposition, vacuum evaporation, spin coating, casting, LB method, inkjet printing, laser printing or LITI methods may be used, but are not limited thereto. Vacuum evaporation means heating and coating a material onto a substrate in a vacuum environment.

[0116] In the present invention, the various layers are preferably formed by vacuum evaporation, wherein the layers can be formed at a temperature of about 100-500° C. and at a temperature of about 10 -8 -10 -2 Torr vacuum and approx. The vacuum evaporation is carried out at a rate of 10 -6 -10 -2 Torr, preferably 10 -5 -10 -3 Torr. The rate is about More preferably, about

[0117] In addition, it should be noted that the materials used to form each layer described in the present invention can be formed into a film alone and used as a single layer, or can be mixed with other materials to form a film and used as a single layer. It can also be a stacked structure between layers formed into films alone, a stacked structure between layers formed into films after mixing, or a stacked structure of layers formed into films alone and layers formed into films after mixing.

[0118] The following examples are intended to better explain the present invention, but the scope of the present invention is not limited thereto.

[0119] I. Compound Preparation Examples

[0120] The present invention is described in detail below with reference to the accompanying drawings and examples. The raw materials involved in the synthesis examples of the present invention can be purchased from the market or prepared by conventional preparation methods in the art;

[0121] Preparation of intermediate C1:

[0122]

[0123] Under nitrogen protection, in a round-bottom flask, raw material A1 (11.47 g, 30 mmol), raw material B1 (9.52 g, 30 mmol), K 2 CO 3 (13.82 g, 100 mmol), tetrahydrofuran (160 mL), water (60 mL), nitrogen was passed through for 50 min to replace the air, and Pd(PPh 3 ) 4 (0.69 g, 0.6 mmol), heated to reflux for 15 h under nitrogen protection. The reaction solution was taken for TCL detection to find that the raw material A1 had reacted completely. After the reaction was completed, the reaction system was naturally cooled to room temperature, the solvent was removed by rotary evaporation, 150 ml of dichloromethane was added to the residue to dissolve, 120 ml of water was added to wash, poured into a separatory funnel and shaken, and then allowed to stand for stratification. After separation, the aqueous phase was extracted with dichloromethane (60 ml*3), the organic phases were combined and dried with anhydrous magnesium sulfate, filtered, and the filtrate was subjected to rotary evaporation to remove dichloromethane to obtain a crude product, which was purified by silica gel column chromatography to obtain intermediate C1.

[0124] Intermediate C was prepared by the synthesis method of intermediate C1, except that different raw materials were used, as shown in Table 1;

[0125] Table 1

[0126]

[0127]

[0128]

[0129] Preparation of intermediate Q13:

[0130]

[0131] Under nitrogen protection, in a round-bottom flask, raw material O13 (6.96 g, 30 mmol), raw material P13 (7.62 g, 30 mmol), KOAC (4.91 g, 50 mmol), dioxane (120 ml), water (100 ml) were added in sequence, nitrogen was passed through for 40 min to replace the air, and Pd(dppf)Cl was added. 2 (0.15g, 0.2mmol), heated to reflux for 12h under nitrogen protection. TCL detection of the reaction solution found that the raw material O13 reacted completely. After the reaction was completed, the reaction system was naturally cooled to room temperature, poured into a separatory funnel, shaken, and then allowed to stand for stratification. After separation, the aqueous phase was extracted with dichloromethane (50ml*3), the organic phases were combined and dried with anhydrous magnesium sulfate, filtered, and the filtrate was evaporated to remove dichloromethane to obtain intermediate Q13. LC-MS: Measured value: 280.41 ([M+H]+), accurate mass: 279.14. Preparation of intermediate F1:

[0132]

[0133] Under nitrogen protection, in a round-bottom flask, intermediate C1 (6.69 g, 15 mmol), raw material E1 (4.58 g, 20 mmol), K 2 CO 3 (6.91 g, 50 mmol), tetrahydrofuran (150 mL), water (50 mL), nitrogen was passed through for 35 min to replace the air, and Pd(PPh 3 ) 4 (0.35 g, 0.3 mmol), heated to reflux for 18 h under nitrogen protection. The reaction solution was taken for TCL detection to find that the intermediate C1 reacted completely. After the reaction was completed, the reaction system was naturally cooled to room temperature, the solvent was removed by rotary evaporation, 150 ml of dichloromethane was added to the residue to dissolve, 100 ml of water was added to wash, poured into a separatory funnel and shaken, and then allowed to stand for stratification. After separation, the aqueous phase was extracted with dichloromethane (50 ml*3), the organic phases were combined and dried with anhydrous magnesium sulfate, filtered, and the filtrate was subjected to rotary evaporation to remove dichloromethane to obtain a crude product, which was purified by silica gel chromatography to obtain intermediate F1.

[0134] Intermediate F was prepared by the synthesis method of intermediate F1, except that different raw materials were replaced, as shown in Table 2;

[0135] Table 2

[0136]

[0137]

[0138]

[0139]

[0140] Example 1: Synthesis of Compound 1

[0141]

[0142] Under nitrogen protection, in a round-bottom flask, intermediate F1 (4.68 g, 10 mmol), raw material G1 (2.45 g, 12 mmol), K 2 CO 3 (4.15g, 30mmol), tetrahydrofuran (50mL), water (30mL), nitrogen was passed for 40min to replace the air, palladium acetate (0.0225g, 0.10mmol), 2-dicyclohexylphosphine-2',4',6'-triisopropylbiphenyl (0.0954g, 0.20mmol) were added, and the reaction solution was heated under reflux for 26h under nitrogen protection. The reaction solution was taken for TCL detection to find that the intermediate F1 was completely reacted. After the reaction was completed, the reaction system was naturally cooled to room temperature, the solvent was removed by rotary evaporation, and the residue was dissolved in 180ml of dichloromethane, washed with 120ml of water, poured into a separating funnel, shaken, and then allowed to stand for stratification. After separation, the aqueous phase was extracted with dichloromethane (80ml*3), the organic phases were combined, dried with anhydrous magnesium sulfate, filtered, and the filtrate was evaporated to remove dichloromethane to obtain a crude product, which was purified by silica gel column chromatography to obtain compound 1.

[0143] Other compounds were prepared by a synthetic method similar to compound 1, except that different reactants were replaced. The raw materials or intermediates used are shown in Table 3:

[0144] Table 3

[0145]

[0146]

[0147]

[0148]

[0149]

[0150] Example 26: Synthesis of Compound 462:

[0151]

[0152] Under nitrogen protection, in a round-bottom flask, raw material A26 (4.69 g, 15 mmol), intermediate F26 (5.01 g, 15 mmol), n-butyl lithium (3.21 g, 50 mmol), tetrahydrofuran (150 mL), water (50 mL) were added in sequence, and heated to reflux for 18 h under nitrogen protection. TCL detection of the reaction solution found that the raw material A26 reacted completely. After the reaction was completed, the reaction system was naturally cooled to room temperature, the solvent was removed by rotary evaporation, 150 ml of dichloromethane was added to the residue to dissolve, 100 ml of water was added to wash, poured into a separatory funnel and shaken, and then allowed to stand for stratification. After separation, the aqueous phase was extracted with dichloromethane (50 ml * 3), the organic phases were combined and dried with anhydrous magnesium sulfate, filtered, and the filtrate was evaporated to remove dichloromethane to obtain a crude product, which was purified by silica gel column chromatography to obtain compound 462. Elemental analysis (C 41 H 31 N 3 ) Theoretical value: C, 87.05; H, 5.52; N, 7.43; Test value: C, 87.02; H, 5.57; N, 7.41. LC-MS: Measured value: 566.36 ([M+H] + ), exact mass: 565.25. 1 H NMR(400MHz,Chloroform-d)δ9.27(d,1H),8.34(d,1H),8.12–7.60(m,11H),7.58–7.17(m,6H),2.54(dd,12H).

[0153] II. Device Preparation Example

[0154]

[0155] The structures of the comparative compounds NCG-1, NCG-2, NCG-3, NCG-4, NCG-5, NCG6, NCG-7, NCG-8 and NCG-9 are as above, and the above materials are all commercially available.

[0156] In order to illustrate the application of the compound of the present invention as a charge generation layer in an organic electroluminescent device, a stacked device (two-layer blue light device) was constructed to study the performance of the material of the present invention. It should be noted that since the stacked device needs to take the device optical design into consideration, the film thickness and structure of the device need to be redesigned and adjusted compared to the single-layer device structure, and it is not simply a matter of stacking the single-layer devices.

[0157] The following describes in detail the application effect of the compound synthesized by the present invention as a charge generation layer (CGL) material in a stacked organic electroluminescent device in a device through device examples 1-26 and device comparison examples 1-9. Compared with device example 1, device examples 2-26 and device comparison examples 1-9 have exactly the same manufacturing process for the devices, and use the same substrate material and electrode material, and the film thickness of the electrode material is also consistent. The difference is that the charge generation layer (CGL) material in the device has changed. The specific device structure is shown in Table 4. For the convenience of presentation, the device structure in Table 4 only lists the material structure of the charge generation layer (CGL), and the other layer structures and film thicknesses are omitted because they are consistent.

[0158] Table 4

[0159] Device Embodiment Corresponding CGL layer / film thickness Device Comparison Example 1 NCG-1:Yb=98:2 10nm Device Comparison Example 2 NCG-2:Yb=98:2 10nm Device Comparison Example 3 NCG-3:Yb=98:2 10nm Device Comparison Example 4 NCG-4:Yb=98:2 10nm Device Comparison Example 5 NCG-5:Yb=98:2 10nm Device Comparison Example 6 NCG-6:Yb=98:2 10nm Device Comparison Example 7 NCG-7:Yb=98:2 10nm Device Comparison Example 8 NCG-8:Yb=98:2 10nm Device Comparison Example 9 NCG-9:Yb=98:2 10nm Device Example 1 Compound 1: Yb = 98:2 10nm Device Example 2 Compound 2: Yb = 98:2 10nm Device Example 3 Compound 3: Yb = 98:2 10nm Device Example 4 Compound 4: Yb = 98:2 10nm Device Example 5 Compound 6: Yb = 98:2 10nm Device Example 6 Compound 10: Yb = 98:2 10nm Device Example 7 Compound 19: Yb = 98:2 10nm Device Example 8 Compound 28: Yb = 98:2 10nm Device Example 9 Compound 43: Yb = 98:2 10nm Device Example 10 Compound 46: Yb = 98:2 10nm Device Example 11 Compound 58: Yb = 98:2 10nm Device Example 12 Compound 107: Yb = 98:2 10nm Device Example 13 Compound 115: Yb = 98:2 10nm Device Example 14 Compound 116: Yb = 98:2 10nm Device Example 15 Compound 62: Yb = 98:2 10nm Device Example 16 Compound 60: Yb = 98:2 10nm Device Example 17 Compound 89: Yb = 98:2 10nm Device Example 18 Compound 127: Yb = 98:2 10nm Device Example 19 Compound 172: Yb = 98:2 10nm Device Example 20 Compound 180: Yb = 98:2 10nm Device Example 21 Compound 173: Yb = 98:2 10nm Device Example 22 Compound 218: Yb = 98:2 10nm Device Example 23 Compound 223: Yb = 98:2 10nm Device Example 24 Compound 352: Yb = 98:2 10nm Device Example 25 Compound 356: Yb = 98:2 10nm Device Example 26 Compound 462: Yb = 98:2 10nm

[0160] Device Example 1

[0161] The specific preparation process is as follows:

[0162] like Figure 1As shown, the transparent substrate layer 1 is transparent glass, the anode layer 2 is Ag (100nm), and on the clean anode layer 2, a vacuum evaporation device is used to evaporate HT-1 and P-1 with a film thickness of 10nm as the first hole injection layer 3, and the mass ratio of HT-1 and P-1 is 97:3. Then, HT-1 with a thickness of 20nm is evaporated as the first hole transport layer 4. Then, EB-1 with a thickness of 5nm is evaporated as the first electron blocking layer 5. After the evaporation of the above-mentioned first electron blocking layer 5 material is completed, the first light-emitting layer 6 of the organic electroluminescent device is prepared, and its structure includes BH-1 used as the main material, BD-1 as the doping material, the doping ratio of the doping material is 3% by weight, and the first light-emitting layer has a film thickness of 20nm. After the above-mentioned first light-emitting layer 6, HB-1 is continuously evaporated, and the film thickness is 5nm, as the first hole blocking layer 7. On the above-mentioned first hole blocking layer 7, ET-1 and Liq are continuously evaporated, and the mass ratio of ET-1 and Liq is 1:1. The vacuum-deposited film thickness of the material is 20nm, and this layer is the first electron transport layer 8. On the first electron transport layer 8, a charge generation layer (CGL layer) 9 is evaporated by a vacuum evaporation device, and its structure is compound 1: Yb (the doping ratio of Yb is 2% by weight), and the film thickness is 10nm. Then, HT-1 and P-1 with a film thickness of 10nm are continued to be evaporated as the second hole injection layer 10, and the mass ratio of HT-1 and P-1 is 97:3. Then HT-1 with a thickness of 50nm is evaporated as the second hole transport layer 11. EB-1 with a thickness of 5nm is then evaporated as the second electron blocking layer 12. After the evaporation of the above-mentioned second electron blocking layer 12 material is completed, the second light-emitting layer 13 of the OLED light-emitting device is prepared, and its structure includes BH-1 used as the main material, BD-1 as the doping material, the doping ratio of the doping material is 3% by weight, and the second light-emitting layer 13 has a film thickness of 20nm. After the second light-emitting layer 13, HB-1 was continuously evaporated to a thickness of 5 nm as the second hole blocking layer 14. On the second hole blocking layer 14, ET-1 and Liq were continuously evaporated to a thickness of 30 nm. This layer was the second electron transport layer 15. On the second electron transport layer 15, a LiF layer with a thickness of 1 nm was formed by a vacuum evaporation device. This layer was the second electron injection layer 16. On the second electron injection layer 16, a Mg:Ag electrode layer with a thickness of 16 nm was formed by a vacuum evaporation device. The mass ratio of Mg to Ag was 1:9. This layer was used as the cathode layer 17. On the cathode layer 17, 65 nm of CP-1 was vacuum evaporated to form a capping layer 18.

[0163] After completing the production of the electroluminescent device according to the above steps, the efficiency data and light decay life of the device are measured. The results are as follows:

[0164] As shown in Table 5. The molecular structure formula of the relevant materials is shown below:

[0165]

[0166]

[0167] The device was tested for driving voltage, current efficiency, CIEx, CIEy and LT95 life. Driving voltage, current efficiency, CIEx, and CIEy were tested using an IVL (current-voltage-luminance) test system (Suzhou Fushida Scientific Instrument Co., Ltd.) at a current density of 10 mA / cm 2 LT90 refers to the time it takes for the device brightness to decay to 90% of the initial brightness. The current density during the test is 20mA / cm 2 The life test system is an EAS-62C OLED device life tester produced by Japan System Technology Co., Ltd. The efficiency and life data of each device embodiment and device comparative example are shown in Table 5.

[0168] Table 5

[0169]

[0170]

[0171] It can be seen from Table 5 above that when the compounds of the present invention are used as CGL materials in stacked devices, the device voltage decreases, and the device efficiency and device life are improved compared with the comparative materials, which further shows that the compounds of the present invention have good technical effects when used as CGL materials in stacked OLED devices.

[0172] Thus, it can be seen that the present application compound, by limiting o-phenanthroline and cyano structure, and bridged by specific aromatic or heteroaromatic groups, can effectively improve the molecular plane stacking ability, increase the interaction between molecules. Meanwhile, the present application compound has a strong electron-withdrawing ability, can effectively improve electron injection and transmission ability, improve electron injection and transmission ability, thereby reducing the device driving voltage. Further, by adding a specific bridging group, the symmetry of the molecule is effectively destroyed, the three-dimensional structure of the molecule is increased, the film crystallinity of the molecule is suppressed, the stability and durability of the material are promoted, and it is conducive to improving device efficiency and lifespan. And, because the compound of the present invention has good electron-withdrawing ability, stability and electronic tolerance, it is used as the n-type material of CGL layer, and can form a stable N-metal coordination bond with metals such as Yb, form a stable and smooth organic-metal doped film, suppress the oxidation of metal, and it is conducive to improving charge generation and device stability.

[0173] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

[0174] For those skilled in the art, several modifications and improvements may be made without departing from the concept of the present invention, all of which belong to the protection scope of the present invention. The protection scope of the present invention shall be based on the attached claims.

Claims

1. A compound containing o-phenanthroline and a cyano structure, characterized in that, The structure of the compound containing o-phenanthroline and cyano structure is shown in general formula (1): In the general formula (1), X1, X2, X3, X4, X5, and X6 are each independently represented by CH or N; at most one of X1, X2, X3, X4, X5, and X6 is represented by N; Ar1 ​​and Ar2 are each independently represented by substituted or unsubstituted phenyl, substituted or unsubstituted naphthyl, substituted or unsubstituted biphenyl, substituted or unsubstituted terphenyl, substituted or unsubstituted pyridyl, or the structure represented by the general formula (2); one and only one of Ar1 and Ar2 is represented by the structure represented by the general formula (2); L1, L2, and L3 are each independently represented by a single bond, substituted or unsubstituted phenylene, substituted or unsubstituted naphthylene, biphenylene, substituted or unsubstituted terphenylene, or substituted or unsubstituted pyridylene; L1, L2, and L3 may be the same or different; In the general formula (2), R1, R2, R3, R4, R5, R6, R7, and R8 are each independently a hydrogen atom, a substituted or unsubstituted C1-C6 alkyl group, a substituted or unsubstituted phenyl group, or a substituted or unsubstituted naphthyl group, and at least one of R1-R8 does not exist to serve as a connection site; The substituent of the substitutable group may be selected from deuterium, tritium, halogen, cyano, C1-C6 alkyl or phenyl.

2. A compound containing o-phenanthroline and a cyano structure according to claim 1, characterized in that, The structure of the compound containing o-phenanthroline and cyano structure is shown in general formula (1-1): In the general formula (1-1), X1, X2, X3, X4, X5, and X6 are each independently CH or N; at most one of X1, X2, X3, X4, X5, and X6 is N; Ar2 is substituted or unsubstituted phenyl, substituted or unsubstituted naphthyl, substituted or unsubstituted biphenyl, substituted or unsubstituted terphenyl, or substituted or unsubstituted pyridyl; L3 is substituted or unsubstituted phenylene, substituted or unsubstituted naphthylene, biphenylene, substituted or unsubstituted terphenylene, or substituted or unsubstituted pyridylene; R1, R2, R3, R4, R5, R6, R7, and R8 are each independently a hydrogen atom, a substituted or unsubstituted C1-C6 alkyl group, a substituted or unsubstituted phenyl group, or a substituted or unsubstituted naphthyl group, and at least one of R1-R8 does not exist as a connection site; The substituents of the substitutable group are optionally selected from protium, deuterium, tritium, halogen, cyano, C1-C6 alkyl or phenyl; Preferably, the structure of the compound containing o-phenanthroline and a cyano structure is as shown in general formula (1-2): In the general formula (1-2), X1, X2, X3, X4, X5, and X6 are each independently CH or N; at most one of X1, X2, X3, X4, X5, and X6 is N; Ar2 is substituted or unsubstituted phenyl, substituted or unsubstituted naphthyl, substituted or unsubstituted biphenyl, substituted or unsubstituted terphenyl, or substituted or unsubstituted pyridyl; L3 is substituted or unsubstituted phenylene, substituted or unsubstituted naphthylene, biphenylene, substituted or unsubstituted terphenylene, or substituted or unsubstituted pyridylene; R2, R3, R4, R5, R6, R7, and R8 are each independently a hydrogen atom, a substituted or unsubstituted C1-C6 alkyl group, a substituted or unsubstituted phenyl group, or a substituted or unsubstituted naphthyl group, and at least one of R1-R8 does not exist as a connection site; The substituent of the substitutable group may be selected from deuterium, tritium, halogen, cyano, C1-C6 alkyl or phenyl.

3. A compound containing o-phenanthroline and a cyano structure according to claim 1, characterized in that, The structure of the compound containing o-phenanthroline and a cyano structure is shown in any one of general formulas (1-3) to (1-6): In general formula (1-3) to general formula (1-6), X1, X2, X3, X4, X5, and X6 are each independently CH or N; at most one of X1, X2, X3, X4, X5, and X6 is N; Ar2 is substituted or unsubstituted phenyl, substituted or unsubstituted naphthyl, substituted or unsubstituted biphenyl, substituted or unsubstituted terphenyl, or substituted or unsubstituted pyridyl; L3 is substituted or unsubstituted phenylene, substituted or unsubstituted naphthylene, biphenylene, substituted or unsubstituted terphenylene, or substituted or unsubstituted pyridylene; R1, R2, R3, R4, R5, R6, R7, and R8 are each independently a hydrogen atom, a substituted or unsubstituted C1-C6 alkyl group, a substituted or unsubstituted phenyl group, or a substituted or unsubstituted naphthyl group, and at least one of R1-R8 does not exist as a connection site; The substituent of the substitutable group may be selected from deuterium, tritium, halogen, cyano, C1-C6 alkyl or phenyl. Preferably, the structure of the compound containing o-phenanthroline and a cyano structure is as shown in any one of general formulas (1-7) to (1-10): In general formula (1-7) to general formula (1-10), X1, X2, X3, X4, X5, and X6 are each independently represented by CH or N; at most one of X1, X2, X3, X4, X5, and X6 is represented by N; Ar2 is represented by substituted or unsubstituted phenyl, substituted or unsubstituted naphthyl, substituted or unsubstituted biphenyl, substituted or unsubstituted terphenyl, or substituted or unsubstituted pyridyl; L3 is represented by substituted or unsubstituted phenylene, substituted or unsubstituted naphthylene, biphenylene, substituted or unsubstituted terphenylene, or substituted or unsubstituted pyridylene; R2, R3, R4, R5, R6, R7, and R8 are each independently a hydrogen atom, a substituted or unsubstituted C1-C6 alkyl group, a substituted or unsubstituted phenyl group, or a substituted or unsubstituted naphthyl group, and at least one of R1-R8 does not exist as a connection site; The substituent of the substitutable group may be selected from deuterium, tritium, halogen, cyano, C1-C6 alkyl or phenyl.

4. A compound containing o-phenanthroline and a cyano structure according to any one of claims 1 to 3, characterized in that: In the general formula (1), L1, L2, and L3 are independently selected from any one of the following structures: single bond, Preferably, L1, L2, and L3 are independently selected from any one of the following structures: single bond, 5. A compound containing o-phenanthroline and a cyano structure according to any one of claims 1 to 3, characterized in that: The Ar1 and Ar2 are independently selected from any one of the following structures: And one and only one of Ar1 and Ar2 is represented by any one of the following structures:

6. A compound containing o-phenanthroline and a cyano structure according to claim 1, characterized in that, The compound containing o-phenanthroline and cyano structure is any one of the following structures:

7. A stacked organic electroluminescent device, comprising a first electrode, a second electrode, a first light-emitting unit, a second light-emitting unit and a charge generation layer, wherein the first light-emitting unit, the second light-emitting unit and the charge generation layer are located between the first electrode and the second electrode, and the charge generation layer is located between the first light-emitting unit and the second light-emitting unit, characterized in that: The charge generation layer comprises the compound containing o-phenanthroline and a cyano structure according to any one of claims 1 to 6.

8. The stacked organic electroluminescent device according to claim 7, characterized in that: The first light-emitting unit includes a first hole transport region, a first light-emitting layer and a first electron transport region, and the second light-emitting unit includes a second hole transport region, a second light-emitting layer and a second electron transport region.

9. The stacked organic electroluminescent device according to claim 7, characterized in that: The charge generation layer further includes a metal material.

10. The stacked organic electroluminescent device according to claim 9, characterized in that: The metal material is Li, Ca, Ag, Cs or Yb.